Guatemala : Article IV Consultation: Staff Report; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report ;, 2012)
This Article IV Consultation reports that macroeconomic developments in Guatemala have been broadly positive since 2010. Although the external current account deficit widened in 2011, the surplus in the capital account was larger, partly owing to banks' increased access to foreign credit lines. Executive Directors have welcomed Guatemala's economic recovery and the favorable outlook, considering that the policy stance for 2012 is broadly appropriate. Directors have also encouraged the authorities to improve public expenditure management.